Small producer....big business! - Inter-American Institute for Cooperation on Agriculture (Inter-American Institute for Cooperation on Agriculture, 2010)
Small producers, i.e., both farmers and food processors, are a big business in agriculture in the Caribbean. Their numbers far outweigh their relatively larger counterparts. Despite the difficult conditions under which they operate, including marginal lands, limited access to credit and the virtual non-existence of risk mitigation mechanisms, the contributions of these micro and small entrepreneurs to economic development, social stability and food security are big by comparison to their size...